American design (National Gallery Suite No.3) for orchestra - BALES, Richard (Alexander Broude, 1957)
Sign from the Black HorsenFigureheadnRag DollnAngel Gabriel WeathervanenCigar stone IndiannWhiskey FlasknDowry or Hope ChestnBaseball player